Rekonstruksi Pembelajaran Pendidikan Agama Kristen yang Adaptif terhadap Perkembangan Teknologi di Era Digital - Adika Putri Manein; Agnes Tirsha Tulong; Yuriske Fillia Salindeho (Peneliti.net, 2026)
The rapid development of digital technology has significantly transformed the ways students access, process, and utilize information in the learning process. These changes require Christian Religious Education (CRE) to adapt its instructional practices in order to remain relevant to the characteristics and learning needs of students in the digital era. However, existing studies indicate that Christian Religious Education is still predominantly characterized by teacher-centered instruction, lecture-based methods, and limited integration of technology into pedagogically meaningful learning experiences. Consequently, Christian Religious Education is often perceived as monotonous, less engaging, and insufficiently responsive to the learning preferences of today's digital generation. This article aims to reconstruct Christian Religious Education learning to become more adaptive to technological developments in the digital era while preserving its fundamental mission of fostering faith, Christian character, and holistic student development. This study employs a qualitative method using a literature review approach by critically analyzing books, scholarly articles, and other relevant academic sources on Christian Religious Education, digital learning, and educational technology. The findings suggest that the reconstruction of Christian Religious Education learning should emphasize student-centered, participatory, contextual, collaborative, and reflective learning experiences supported by the appropriate integration of digital technologies. In this context, digital technologies, including artificial intelligence, should function as instructional support tools that enrich learning experiences rather than replace the role of teachers. Therefore, Christian Religious Education needs to continuously adapt its learning practices to technological advancements in order to remain relevant, meaningful, and effective in achieving its educational goals in the digital era.